(untitled) (Italian Journal of Public Health, 2017)
Background: acne vulgaris, is one of the most common skin disorder. Previous studies about the role of smoke in the pathogenesis of acne reported contradictory results. The aim of this study was to conduct a case-control study investigating the relationship between tobacco smoking and acne. Methods: a case-control study was performed during the period September 2009 - February 2010. A questionnaire was administrated to each participant, to assess the association acne - smoke. Cases were outpatients of the Dermatologic Ambulatory of the “Fiorini” Hospital, Sapienza University of Rome (Italy). Controls were age and gender-matched to the cases. The ratio cases-controls was 1:2. A univariate and a multiple logistic regression analysis were conducted; Odds Ratio (OR ) and the relative 95% confidence interval (95%CI) were assessed. The statistical significance was set at p < 0.05. Results: crude OR for the association acne - smoke was 7.26 (IC=2.27-23.18); adjusted OR for sex and age was 5.47 (IC=1.67-17.97). Of 93 cases, 6 had a severe grade of acne (6.5%), 19 had an intermediate grade of acne (20.4%), and 68 had a mild grade of acne (73.1%). No one of the smokers had a severe grade of acne, one had an intermediate grade of acne and 11 had mild acne; these differences are not statistically significant. Conclusions: the association between acne and smoke shows an increased risk (OR=7.26) with a statistically significant CI. Moreover, people ≥ 18 years of age have twice the risk compared to persons < 18 years of age (OR=2.31).